Síndrome de burnout e qualidade de vida: estudo com professores universitários da área da saúde - Fonsêca, Leila de Cássia Tavares da (2016)
Introduction: Burnout syndrome (SB) is a psychosocial phenomenon triggered by exercise, which generates permanent stress on the individual, resulting from a constant and repetitive emotional pressure related to daily activities, especially in professionals who work in direct contact with people. SB is considered a serious public health problem and the teaching profession is a category of risk, because it has a strong incidence of elements that lead to the syndrome, which is characterized by four dimensions: illusion for work; Psychic wear; Sloth and guilt. Quality of life, in turn, adds aspects that are associated with the environment, conditions and work organization. Therefore, the importance of studying its association with SB. Objectives: to analyze the association of Burnout Syndrome and Quality of Life in university health professors; Characterize the social, demographic and professional conditions of university professors in the health area; To investigate the dimensions of Burnout Syndrome, according to the CESQT, in university health professors; To verify how university professors perceive quality of life, according to WHOWOL-bref; Investigate how the university professors participating in the study are affected by Burnout Syndrome. Methodology: This was a causal research, with a quantitative approach, with 178 teachers from the Health Sciences Center (CCS) and 105 from the Center of Medical Sciences (CCM), whose sample was obtained by stratified sampling technique with proportional allocation And the collection made through random sampling technique for accessibility. In order to do so, validated questionnaires were used in Brazil: Questionnaire for the identification of Burnout Syndrome - "Questionnaire for the Evolution of Burning Syndrome by the Work-SCQT-PE" and the Quality of Life Questionnaire - WHOQOL-bref. For data analysis, the recommendations described in the instrument manuals were followed. Thus, the test of association (chi-square) between the dimensions of burnout and the domains of quality of life was performed. Results: 46 (25.8%) individuals with burnout symptoms were found in CCS and 33 (31.4%) were found in CCM. In general, CCS teachers perceive quality of life as good, while CCM teachers rated it as a regular grade. In addition, the illusion of work and guilt dimensions were significantly associated with the components of quality of life, thus demonstrating the strong influence of this on the composition of the syndrome symptoms. Conclusion: SB is a problem among university professors in the health area and interferes in the quality of life of these professionals. It is recommended to rethink the organization of teaching work with a view to preventing this phenomenon that can affect the physical, mental and social health of individuals, bringing negative consequences for the institution regarding the educational process.